Transportation network modeling and calibration - Jeihani Koohbanani, Mansoureh, 1973-; Ardeshiri, Anam (Transportation engineering collection., 2017)
Transportation scientists employ modeling and simulation techniques to capture the complexities of transportation systems and develop and assess solutions to alleviate existing and future transportation-related problems. This book introduces transportation engineering students and junior engineers to the concept of transportation network modeling, network coding, model calibration and validation, and model evaluation. Travel demand models are sensitive to demographic changes and can explain and forecast how a new transportation supply system leads to a new transportation demand pattern. This book also describes how demand models evolved from trip-based to the newer generation of activity-based and agent-based to overcome some of the shortcomings of the four-step approach and improve models' prediction power.